A scorm compliant course framework for distance learning - Sönmezer, Barış İbrahim. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2004., 2004)
The purpose of the thesis is to construct a distance learning system for the educational content of the CMPE 150 course named "Introduction to Computing". Actually, a framework has been developed to transport other departmental courses to the electronic media.The whole content is constructed from the beginning. Seven subjects are chosen for delivery, which are about the basic concepts in computer engineering. The aim is to give these basics to the new computer engineer candidates. The electronic content is prepared using advanced web technologies. As the Internet is widespread used in the World, WWW is the best method for the delivery of the electronic content. The content should be supported with visual material to attract the attention of the audience. The content, supported with interactive animations, will be more understandable and more striking. Macromedia Flash is used to construct the interactive animations for the course content. The content should also be compatible with Learning Management Systems developed by different vendors to reach more people and implement reusability. To make the content compatible with LMS software developed by different vendors, the electronic content is organized as Sharable Content Object Reference Model (SCORM) compliant.
Keywords: Distance education.; Computer-assisted instruction.